2019
DOI: 10.1515/cclm-2019-0568
|View full text |Cite
|
Sign up to set email alerts
|

Calcium state estimation by total calcium: the evidence to end the never-ending story

Abstract: BackgroundTotal blood calcium (TCa) is routinely used to diagnose and manage mineral and bone metabolism disorders. Numerous laboratories adjust TCa by albumin, though literature suggests there are some limits to this approach. Here we report a large retrospective study on agreement rate between ionized calcium (iCa) measurement and TCa or albumin-adjusted calcium measurements.MethodsWe retrospectively selected 5055 samples with simultaneous measurements of iCa, TCa, albumin and pH. We subgrouped our patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Although correction formulas have been used to adjust tCa with albumin level, their predicting capacity is diminished by various factors (7). Unlike tCa, iCa is unaffected by altered acid-base status or albumin level, thus making it a more reliable parameter in the assessment of patients' calcium status (8) and health status.…”
Section: Introductionmentioning
confidence: 99%
“…Although correction formulas have been used to adjust tCa with albumin level, their predicting capacity is diminished by various factors (7). Unlike tCa, iCa is unaffected by altered acid-base status or albumin level, thus making it a more reliable parameter in the assessment of patients' calcium status (8) and health status.…”
Section: Introductionmentioning
confidence: 99%
“…1 Approximately 15% is bound to organic and inorganic anions, 40% is bound to proteins, particularly albumin, and 45% circulates as active ionised calcium. 2 This last portion is strictly controlled by parathyroid hormone and vitamin D. 3 Total serum calcium concentration substantially varies on the serum concentration of albumin and hydration status without any alteration in the concentration of ionised calcium. [4][5][6][7] Hence, measuring only total serum calcium might be misleading.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of correlation between tCa and miCa is of great concern in human and veterinary medicine. 17,18 In a general canine population, tCa appears poorly sensitive but quite specific for assessing calcium status, suggesting a high rate of false-negative results, but a few false-positive results based upon previous studies. 9,10 This contrasts with the present study, as only 55% of dogs with total hypercalcemia and 60% of dogs with total hypocalcemia had iHyperCa and iHypoCa, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Adjusting tCa for albumin or total protein concentrations is inefficient for this purpose. 9,10,17 A recent study evaluated a tCa threshold of 12 mg/dL in normophosphatemic dogs and found a high Spe, PPV, and NPV (100%, 93%, and 97%, respectively) for iHyperCa. This threshold, however, was inaccurate for confirming iHyperCa in hyperphosphatemic dogs owing to the low PPV (19%).…”
Section: Discussionmentioning
confidence: 99%